Calorimetric, spectroscopic and molecular modelling insight into the interaction of gallic acid with bovine serum albumin. (July 2018) - Khatun, Samima; Riyazuddeen,; Yasmeen, Shama; Kumar, Amarjeet; Subbarao, Naidu
Highlights: GA quenches the fluorescence spectra of BSA in a static manner. GA primarily bound to near sub-domain IIA (Sudlow's site I) of BSA. GA binds to BSA through hydrogen bonding and van der Waals forces. Secondary structure alteration of BSA was studied by CD spectroscopy. MD simulation result revealed that GA binding on site-I of BSA is stable. Abstract: Gallic acid (GA), a naturally occurring plant phenolic acid, effectively used as antioxidant, anti-carcinogenic, antifungal, anti-inflammatory and in anti-human rhinovirus activities. The present study reports in vitro interaction studies of Gallic acid (GA) with bovine serum albumin (BSA) by using isothermal titration calorimetric (ITC), fluorescence, circular dichroism (CD) and molecular modelling studies. The association constant (Ka ), standard enthalpy change (Δ H o ), standard entropy change (Δ S o ) and standard Gibbs energy change (Δ G o ) were obtained from ITC. The fluorescence results indicate that there was static quenching mechanism in the interactions of GA with BSA. The synchronous and 3D fluorescence spectroscopy confirms conformational alteration of BSA in presence of GA which is further supported by CD. Molecular docking analysis highlighted that GA binds at Sudlow site I of BSA which also confirmed from site probe experiments. In addition, the molecular dynamics (MD) simulation study of BSA and BSA-GA complex shows that binding of GA at site I of BSA is stable and the binding Gibbs energies from the molecular mechanics/Poisson-Boltzmann surface area method showed that van der Waals forces are the predominant intermolecular forces. This study reflects greater pharmacological significance of GA and highlights its importance in the clinical medicine.